Returns to Potato Research Investment in Nepal - Timsina, Krishna P.; Gaire, Samaya; Ghimire, Yuga N.; Poudel, Hema K.; Devkota, Deepa; Subedi, Sanjiv; Adhikari, Surya P. (Journal of Agriculture and Natural Resources, 2019)
Agricultural research plays a significant role in increment in productivity and contributes to food security. Very few studies on the impact of public research spending on different sectors and commodities in Nepal has been documented. This study was designed to estimate the adoption lags of improved potato varieties and benefits generated by potato improvement research in Nepal. More specifically, the study answers two basic questions: (i) whether investment in potato research is justifiable? and (ii) how long is it taking to replace old improved varieties? We took public annual potato research investments of Nepal from the Fiscal year 2001 to 2017 from Nepal Agricultural Research Council (NARC). The household survey was carried out to estimate the potato varieties coverage in Nepal in 2017. Other secondary data were sourced from the Ministry of Finance, Ministry of Agricultural and Livestock Development, FAO stat, Nepal Rastra Bank and NARC to complement the analysis. We have used a simple economic framework to estimate the benefits generated from agricultural research. The estimated benefit and cost streams were used to calculate Benefit-Cost Ratio (BCR) and Net Present Value (NPV).  Results showed that the majority of the potato researchers had done research related to crop husbandry (seed production and crop managements); while the limited number of researchers had specialized in breeding activities. The annual growth rate of potato productivity was 214.49 kg per annum per ha which had increased at the rate of 1.76 percent per annum compound growth rate. The results revealed that the average weighted age of improved potato varieties was 21.83 years and each NPR. investment on potato research has given 508 NPR. and NPR. 13760 million NPV at a 12 percent discount factor during the last 17 years. Similarly, the contribution of potato research to GDP and AGDP was found 0.323% and 0.989% respectively. Therefore, future investment and focus should be concentrated on potato research and scaling up activities, and reducing variety adoption lag to obtain additional benefits from potato research investment.